CONTINUOUS CULTURES OF PLASMODIUM FALCIPARUM ESTABLISHED IN TANZANIA FROM PATIENTS WITH ACUTE MALARIA - Florence Urio; Matilda Mkombachepa; Gration Rwegasira; Twilumba Makene; Billy Ngasala; Teddy Mselle; Julie Makani; Lucio Luzzatto (Mediterranean Journal of Hematology and Infectious Diseases, 2021)
Background: Malaria morbidity and mortality, almost entirely from Plasmodium falciparum, are still rampant in Africa: therefore, it is important to study the biology of the parasite and the parasite-host cell interactions. In vitro cultivation of Plasmodium falciparum is most useful for this purpose, as well as for investigating drug resistance and possible new therapies. Here we report that the Trager & Jensen continuous culture of P. falciparum can be established in a laboratory in Tanzania with minimal facilities and with modest expenditure.